Managing the risks of payment systems - Paul S. Turner, Diane B. Wunnick (John Wiley & Sons, Inc., 2003)
This book is about the risks that business entities are likely to encounter in their use of the payment systems employed in the United States. This chapter emphasizes that corporate managers who are responsible for the management of payment risks should understand how the law governing liability for fraudulent checks and funds transfers determines whether the company or the bank is liable for fraud losses and, in addition, should understand whether the wording of the company’s agreements with its bank would make the company liable for a loss even though the law would otherwise make the bank liable for it. Ignorance of the law is not an excuse for poor management of payment systems risks.